2004
DOI: 10.1515/znc-2004-1-206
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aucubin and Catalpol in Plantago Species by Micellar Electrokinetic Chromatography

Abstract: Micellar electrokinetic chromatography (MEKC) was used for the separation and determination of two iridoid glycosides, aucubin and catalpol, in several Plantago species growing in Croatia: P. altissima L., P. argentea Chaix, P. coronopus L., P. holosteum Scop. (subsp. depauperata, subsp. holosteum and subsp. scopulorum), P. lagopus L., P. lanceolata L., and P. maritima L. Hot water extraction (HWE) was applied for the isolation of iridoid substances. Significant differences appeared between the iridoid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 1 publication
(2 reference statements)
1
7
0
Order By: Relevance
“…The aucubin concentration in the Et ranged from 0.98 to 4.18%, whereas in the GL and CT the concentrations were 0.65 and 1.78%, respectively (Table 1). In another study it has been reported that the aucubin concentration in PL is 0.27% (Jurisic et al . 2004), which is much lower than the present results.…”
Section: Resultsmentioning
confidence: 98%
“…The aucubin concentration in the Et ranged from 0.98 to 4.18%, whereas in the GL and CT the concentrations were 0.65 and 1.78%, respectively (Table 1). In another study it has been reported that the aucubin concentration in PL is 0.27% (Jurisic et al . 2004), which is much lower than the present results.…”
Section: Resultsmentioning
confidence: 98%
“…Medicinally, Plantago species are astringents, demulcents, emollients, expectorants, diuretics, antibacterials and antivirals [15]. Phytochemical investigations of Plantago species revealed the presence of iridoids, flavonoids, tannins, triterpenes, saponins, and sterols [15][16][17][18]. Phenolic compounds such as phenylpropanoid glucoside, plantamajoroside, rosmarinic and chlorogenic acid as well as luteolin-7-O-monoglucoside were isolated from Plantago lagopus L. [19].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Aucubin is one of the main components of Plantaginis Semen . 13 Thus, the antiallodynic effect of aucubin, its precursor geniposide acid, and its metabolite catalpol were also tested. Prophylactic repetitive administration of aucubin attenuated the exacerbation of PTX-induced mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%